Discussion on the Structural Design Index and Design Method of Widening and Splicing Lane of Old Asphalt Pavement (Journal of Engineering, 2023)
The splicing design of the existing road and the new road in the expansion project is an important part of the design work. Based on the analysis of the characteristics and the load effect of pavement structure on splicing, this paper points out that tensile crack or shear failure may occur at the splicing under the repeated action of the traffic load on the new/old pavement. According to the current structure design code of asphalt pavement in China, it is proposed that the horizontal tensile stress at the bottom of the splicing layer and the vertical shear stress at other layers of the splicing line should be controlled by adjusting the position and size of the excavated steps in addition to the conventional design index, and put forward the corresponding technical requirements and design process. It can be used for reference in the design of asphalt pavement reconstruction and expansion projects.